2017
DOI: 10.7763/ijmo.2017.v7.574
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Experimental Study of Gas Bubbles Behavior

Abstract: The paper presents theoretical considerations on gas bubbles behavior -analytic calculation of bubble time formation, extra pressure needed for the bubble formation and detachment, bubble size and correlation between the extra pressure and the liquid superficial tension.In order to evaluate the theoretical relation for extra pressure calculation, the results of the tests performed on different metallic perforated plates Ø 60, with a specific number of orifices of different diameters, were used. The extra press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…8), it can be concluded that the average bubble diameter gradually decreases with the increase in temperature below 35°C. This is when the surface tension decreases due to the increase in temperature, and according to Mandrea et al [26] , it was demonstrated that the bubble diameter is proportional to the surface tension of water as follows.…”
Section: Fig 4 Photographs Of Bubbles Taken At Different Condensate C...mentioning
confidence: 99%
“…8), it can be concluded that the average bubble diameter gradually decreases with the increase in temperature below 35°C. This is when the surface tension decreases due to the increase in temperature, and according to Mandrea et al [26] , it was demonstrated that the bubble diameter is proportional to the surface tension of water as follows.…”
Section: Fig 4 Photographs Of Bubbles Taken At Different Condensate C...mentioning
confidence: 99%
“…Bubble formation has a greater impact on pressure drop than the droplet interface. Since the viscosity of the organic and aqueous phases differs significantly, the pressure drop caused by friction on the aqueous phase has the least impact on the total pressure drop [12].…”
Section: Pressure Dropmentioning
confidence: 99%
“…These reductions will facilitate breakup of droplets and bubbles and, thereby, reduce the separation. Mândrea et al studied the generation of gas bubbles by orifices in a water column and showed that the bubble diameter is directly proportional to the surface tension of water. Sadeghi and Vissers showed that the increase of the temperature slightly reduces the size of the bigger bubbles, while it has no significant effect on smaller bubbles.…”
Section: Microscopic Aspects Of Gas Flotationmentioning
confidence: 99%